2011
DOI: 10.1021/ma2016776
|View full text |Cite
|
Sign up to set email alerts
|

Dendronized Polymers with Peripheral Oligo(ethylene oxide) Chains: Thermoresponsive Behavior and Shape Anisotropy in Solution

Abstract: A series of dendronized polymers carrying oligo(ethyleneoxy) peripheral branches have been prepared by postpolymerization functionalization of multiallylic dendronized polymers using a radical addition of mercaptans, namely 2-methoxy(ethoxy)ethanethiol (EO2) and {2-(2-methoxyethoxy)ethoxy)}ethanethiol (EO3). The functionalization proved to be quite efficient, leading to up to 6 or 9 EO chains per monomer repeating unit. A constant T g value was observed independently of the material characteristics, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 66 publications
3
53
1
1
Order By: Relevance
“…23 Second, a previous result indicated that for the same mass concentration a higher molecular weight would result in a lower molar concentration, that is, a more "dilute" polymer solution with less polymer chains. 24 In order to test the dilution effect on the LCST of the homopolymer, the concentration dependence on LCST of homopolymer 3b (M n = 7500 g/mol) ( Figure 2C) and LCSTs of poly(DEAE-NIPAM-AM) 3 with a lower concentration of 0.5 mg/mL ( Figure S5, Supporting Information) were examined. The LCST of 3b was 24.5°C as the concentration was 1.0 mg/mL.…”
mentioning
confidence: 99%
“…23 Second, a previous result indicated that for the same mass concentration a higher molecular weight would result in a lower molar concentration, that is, a more "dilute" polymer solution with less polymer chains. 24 In order to test the dilution effect on the LCST of the homopolymer, the concentration dependence on LCST of homopolymer 3b (M n = 7500 g/mol) ( Figure 2C) and LCSTs of poly(DEAE-NIPAM-AM) 3 with a lower concentration of 0.5 mg/mL ( Figure S5, Supporting Information) were examined. The LCST of 3b was 24.5°C as the concentration was 1.0 mg/mL.…”
mentioning
confidence: 99%
“…Recently, dendronized polymers with peripheral oligo(ethylene oxide) chains show a thermoresponsive behavior and an anisotropic shape in solution [81]. According to the hydrophilic and hydrophobic balance, some polymers exhibited a thermoresponsive behavior in water solution, characterized by a sharp lower critical solution temperature (LCST) transition and a small hysteresis.…”
Section: I) Ii)mentioning
confidence: 99%
“…According to the hydrophilic and hydrophobic balance, some polymers exhibited a thermoresponsive behavior in water solution, characterized by a sharp lower critical solution temperature (LCST) transition and a small hysteresis. These LCST showed an unusual increase with dendronized polymers, which might be correlated to a dilution effect and an increase of polymer hydrophilicity by densification of the dendritic coverage [81]. Moreover, Junk et al published an interesting approach highlighting the structure/property relationship given by the peripheral end-groups and the core of dendrons as modifiers in thermoresponsive dendronized polymers [82].…”
Section: I) Ii)mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28] The T cloud values of thermo-responsive materials are determined by their chemical compositions, i.e., the ratio of the hydrophobic and hydrophilic parts. 1-28 Poly(N-isopropylacrylamide) is a well-known thermo-responsive polymer; it has a clouding point (T cloud ) at 32 1C in aqueous solution.…”
mentioning
confidence: 99%